Relationship of patient safety culture with factors influencing working environment such as working hours, the number of night shifts, and the number of days off among healthcare workers in Japan: a cross-sectional study - Ryosuke Hayashi; Shigeru Fujita; Shuhei Iida; Yoji Nagai; Yoshiko Shimamori; Tomonori Hasegawa (BMC, 2020)
Abstract Background Patient safety culture is defined as a product of individual and group values, attitudes, perceptions, competencies, and patterns of behavior that determine the commitment to, and the style and proficiency of, an organization's health and safety management. Factors influencing healthcare workers' working environment such as working hours, the number of night shifts, and the number of days off may be associated with patient safety culture, and the association pattern may differ by profession. This study aimed to examine the relationship between patient safety culture and working environment. Methods Questionnaire surveys were conducted in 2015 and 2016. The first survey was conducted in hospitals in Japan to investigate their patient safety management system and activities and intention to participate in the second survey. The second survey was conducted in 40 hospitals; 100 healthcare workers from each hospital answered a questionnaire that was the Japanese version of the Hospital Survey on Patient Safety Culture for measuring patient safety culture. The relationship of patient safety culture with working hours in a week, the number of night shifts in a month, and the number of days off in a month was analyzed. Results Response rates for the first and second surveys were 22.4% (731/3270) and 94.2% (3768/4000), respectively. Long working hours, numerous night shifts, and few days off were associated with low patient safety culture. Despite adjusting the working hours, the number of event reports increased with an increase in the number of night shifts. Physicians worked longer and had fewer days off than nurses. However, physicians had fewer composites of patient safety culture score related to working hours, the number of night shifts, and the number of days off than nurses. Conclusions This study suggested a possibility of improving the patient safety culture by managing the working environment of healthcare workers. High number of night shifts may lead to high number of event reports. Working hours, the number of night shifts, and the number of days off may differently influence patient safety culture in physicians and nurses.